Analisis Pengaruh PMDN dan PMA terhadap PDRB di Sumatera Utara - Manihuruk, Frido Evindey; Sitohang, Gresia Septina; Sari, Arsiska (Studi Ekonomi dan Kebijakan Publik, 2024)
Purpose: This study analyzes the effect of Domestic Direct Investment (DDI) and Foreign Direct Investment (FDI) on Gross Regional Domestic Product (GDRP) in North Sumatra Province in the period 2001-2020. Methodology/approach: Secondary data obtained from the North Sumatra Central Bureau of Statistics were used in this study. The data analysis method used in this research was a multiple linear regression method using the Eviews 12 software. Results: The results of this study indicate that the DDI and FDI have a positive and significant effect on Gross Regional Domestic Product in North Sumatra. The coefficient of determination of 92.70% indicates that the model can explain the variation in Gross Regional Domestic Product significantly, and the coefficient value of 7.30% is influenced by other variables outside this study. Limitations: Only tests 2-factor variables that affect stock returns during a certain period are tested. Contribution: This research is expected to provide readers with a better understanding of the contribution of domestic and foreign investment to regional economic growth in North Sumatra. This research is also expected to serve as a reference for local and foreign investment policymakers to improve and stabilize regional economic growth.